2018
DOI: 10.18203/2349-3291.ijcp20185198
|View full text |Cite
|
Sign up to set email alerts
|

Meconium aspiration syndrome: clinical profile, risk factors and outcome in central India

Abstract: Background: Meconium aspiration syndrome (MAS) is a life-threatening respiratory disease affecting some neonates born through meconium-stained amniotic fluid (MSAF). MSAF complicates delivery in approximately 8% to 25% of live births, of which nearly 5% of the neonates born through MSAF develop MAS. The present study was undertaken to find out the prevalence of MSAF and MAS and to study the etiology, risk factors, clinical profile and outcome of MAS.Methods: By purposive sampling technique, all newborns, fulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
4
5
0
Order By: Relevance
“…[5] Almost two-thirds (61%) of births in our sample were through caesarean sections, but mode of delivery was not found to be a risk factor for disease severity. Our finding is similar to that of Khazardoost et al, [14] although other researchers have noted caesarean section as a risk factor for severe disease [4,6,11,13] or that it could even reduce the risk of MAS. [15] Our study did not evaluate indications for caesarean section.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…[5] Almost two-thirds (61%) of births in our sample were through caesarean sections, but mode of delivery was not found to be a risk factor for disease severity. Our finding is similar to that of Khazardoost et al, [14] although other researchers have noted caesarean section as a risk factor for severe disease [4,6,11,13] or that it could even reduce the risk of MAS. [15] Our study did not evaluate indications for caesarean section.…”
Section: Discussionsupporting
confidence: 92%
“…Advanced gestational age (>41 weeks) was not found to be risk factor for disease severity in our study, although other studies have found this to be a risk factor for severe MAS. [6,13,15,19] Our finding may be due to the small number of neonates born after 41 weeks in our sample. Preventing gestation to progress beyond 41 weeks has been shown to decrease the risk of acquiring MAS in developed countries.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Kamble et al conducted a crosssectional observational study which was hospital based, in which the frequency of MSAF was 13.9% and occurrence of MAS out of MSAF was 7.7%. 5 Shilpasri et al found that the incidence of meconium aspiration syndrome was 11%. 6 Rajnish Chaudhary et al concluded that MAS diagnosed most frequently in neonates with fetal distress (42.17%) and in mothers having history of PIH (12.05%).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RD morbidity in low resource settings seems to be greater compared to data of high-income countries [9]. As epidemiological trends show an increasing rate of RD in full-term newborns [10,11] we designed this study with the primary objective to assess and describe clinical aspects, causes and management of RD in full and post-term neonates in a tertiary facility in Yaoundé.…”
Section: Introductionmentioning
confidence: 99%